The Changing Approach to the Interpretation of Statutes - Burrows, John (Victoria University of Wellington Law Review, 2002)
This article was a paper presented at a conference celebrating the career of Sir Ivor Richardson. The author discusses the trends in statutory interpretation in New Zealand. The article notes that early statutory interpretation was literal. However, the introduction of section 5(1) of the Interpretation Act 1999 called for a purposive approach to statutory interpretation, resulting in judges like Sir Ivor Richardson advocating for contextual materials to be presented to the court. The author argues that the purposive approach is preferable, as the judiciary is said to have the freedom to consider contextual materials but is not bound to apply them blindly. However, Professor Burrows notes that the dominant purposive approach is qualified by the existence of fundamental democratic values and clear statutory wording by Parliament. The article concludes that there is now an increasing recognition that the intention of Parliament alone is insufficient in an exercise of statutory interpretation.